KONSEP PENDIDIKAN ISLAM DALAM ALQURAN PERSPEKTIF MUHAMMAD SAYYID AHMAD AL-MUSAYYAR - Muh. Haris Zubaidillah (STIT DARUL ULUM KOTABARU, 2018)
Islamic Education can develop physical and spiritual potential covering all potential of students, both psychomotor, cognitive, and affective potential for the realization of humans who have the main personalities in terms of religion is Insan Kamil and become a servant of Allah SWT who always closer to Him. Education is important for human as an effort to instill and actualize the values ​​of Islam in real life through the Muslims who believe and pious, in accordance with the dignity and degrees of humanity as the khali>fah on earth. The concept of education in Islam refers to the teachings of the Qur'an according Muhammed Sayyid Ahmed Al-Musayyar, there are three basic concepts: firstly, the cultivation of faith and aqidah; secondly, religious education which includes shala>t, amar ma'ru> f nahi> munkar and shabar; and the third, social ethics education. All of that is as inspirated from Luqma>n’s advices to his son.